Uji Aktivitas Antibakteri Ekstrak Jahe Merah (Zingiber officinale var. Rubrum) dan Ekstrak Bawang Putih (Allium sativum) terhadap Streptococcus pyogenes dengan Metode Difusi Cakram - Sitepu, Jenny Novina (Universitas HKBP Nommensen, 2023)
ABSTRACT Background: Infections and antimicrobial resistance remains a major public health worldwide. Therefore, studies regarding the natural therapeutic agent that is safe for humans and specific against bacteria are getting more interest. Objective: This study aimed to investigate the effectiveness of combination red ginger and garlic extract against Streptococcus pyogenes. Methods: This was a laboratory experimental study. The red ginger and garlic extract obtained by maceration extraction method using 70% ethanol and antibacterial activity test was conducted by disk diffusion method. Results: : One way Anova test showed that red ginger extract in 75% and 100% concetrations have significant difference with the control. Garlic extract in 75% and 100% concentrations have significant difference with the control. The higher concentration result wider inhibition zona hambat both in red ginger and garlic extract. Otherwise, red ginger- garlic combination extract showed no significant difference with the control. The widest mean inhibitioin was shown in R50-G50 extract combination which is 2.45mm (±0.3). Post hoc LSD test showed that red ginger 100% that has significant difference with red ginger 25%, so did garlic extract. There was no significant difference between red ginger-garlic combination groups. Conclusion: Red ginger and garlic extract has no synergic effect against Streptococcus pyogenes.